Analytical methods for heat conduction in composites - Mityushev, Vladimir; Obnosov, Yurii; Pesetskaya, Ekaterina; Rogosin, Sergei (Mathematical Modelling and Analysis, 2008)
Analytical methods unifying the study of heat conduction in various type of composite materials are described. Analytical formulas for the effective (macroscopic) conductivity tensor are presented.First Published Online: 14 Oct 2010